Gambaran Kejadian ISPA pada Balita di Wilayah Tempat Pembuangan Akhir Sampah Antang Makassar - Muhammad Sahlan Zamaa; Kamariana; Renaldi; Muhammad Hatta; Andi Wahyuni; Arman Jaya (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2023)
Background: ARI (Acute Respiratory Infection) is one of the main causes of death in Indonesia and worldwide. Many toddlers experience ARI in Antang landfill area. In general, Antang landfill area is far from healthy standard. In Puskesmas Tamangapa, ARI cases on children under five were 0.94% in 2018, 1.03% in 2019, 0.38% in 2020, and 0.44% in 2021. Lack of previous studies conducted research in this area. Aim: This study aimed to describe the incidence of ARI on toddlers. Method: This research was descriptive research in that number of sample was 46 toddlers who had suffered from ARI based on the evaluation of the last 3 months from the Puskesmas Tamangapa selected by total sampling. Data collection applied questionnaire as a research instrument. Results: The results revealed that toddlers with ARI were male 29 (63.0%), good nutritional status was 32 (69.6%), complete immunization status by 31 (67.4%), those whose father smoked were 42 (91.3%), exposed to the smell of light garbage by 21 (45.7%) and the density of the housing was not dense by 38 (82.6%). Conclusion: It concluded that most respondents were male, performed appropriate nutritional status, complete immunization status, their father smokes, exposed to the smell of light garbage and the density of the dwelling is not dense.